Study on the physical properties of printed parts using fresh and recycled polymer powders for additive manufacturing - Chng, Calvin Zuo En (Nanyang Technological University, 2021)
Additive manufacturing, also known as 3D printing, is a relatively new technology that has the potential to bring great changes to the manufacturing industry. Companies around the world are already starting to incorporate additive manufacturing into their processes and supply chains to stay competitive. To save costs, companies are looking into the usage of recycled additive materials in their production. Different types of Polyamide 12 powders were subjected to isothermal and nonisothermal crystallisation. In this study, their crystallinity, melting points, crystallisation time, crystallisation shrinkage and crystal size were studied. Percentage crystallinity was observed to be higher at low isothermal crystallisation temperatures and at slower rates of cooling for non-isothermal crystallisation. Crystallisation time increases exponentially at higher isothermal crystallisation temperatures. Observed trend for re-melting temperatures also points to the presence of at least two crystal phases during crystallisation. Finally, larger crystal size was observed for slower rates of non-isothermal crystallisation. This study was done in collaboration with HP-NTU Digital Manufacturing Corporate Lab and thus is aimed at improving HP’s research, additive manufacturing processes and printers.